Factors that affect the students' outcomes in the pronunciation subjet of the study plan of Licenciatura en idioma inglés opción enseñanza (1999) and the implementation of strategies that could help to reach the pronunciation subject's objetives - Laínez Coreas, María Edén
English pronunciation subject is one of 36 subjects that are included in the study plan for students of Licenciatura en Idioma Ingles, Opcion Enseñanza (Annex II). It is coursed in the second semester of the plan and developed in 16 weeks, four times during the week, one hour a day, including one visit to the English lab per week, making at the end of the course about 128 hours as a total. The main objectives for this subject are to develop the speaking skill, to help students to improve their pronunciation proficiency and accent as well as their English Language comprehension. This subject is based on the teaching of the different features for every single phoneme, in this way students will be able to recognize every phoneme that is quite similar avoiding misunderstanding in a conversation. Although it is clear that in spite of the efforts professors make in order to reach the pronunciation subject’s objectives, these are not totally reached since there are some factors that provoke on students deficiency at the moment of delivering a spontaneous speech, such as large groups, redundant exercises in the English Lab, the amount of time to develop the pronunciation subject and the strategies teachers work with. The main factor that intervenes in the normal development of the pronunciation subject is the size of the groups in which this subject is taught. It can be said that it is in the classroom where the phenomenon starts. Why is it said so? Well in the observed groups the number of students was around 30 – 40 each. So, this number of students is really big for professors’ normal management and performance of the strategies and techniques they use to teach such a subject. Through this, it is not meant, that they do not do a good work, of course not; on the contrary, they even make extra effort to handle such groups of students and to develop the topics and units stated in the syllabus as well to perform their lesson plans.